TEACHING ELEMENTARY STUDENTS TO ANALYZE LITERARY WORKS ON THE BASIS OF PIRLS ASSIGNMENTS - Rajabova Adolat Uktam’s daughter (Sciental Journals Publishing, 2025)
This article reflects on the importance of teaching elementary students to analyze literary works on the basis of PIRLS assignments.
Keywords: international assessment programs, education, innovation, information text, thinking, artistic text, reading literacy, survey, assignment, creative thinking.